2020
DOI: 10.13057/biodiv/d210201
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of Fusarium solani and F. oxysporum by Streptomyces sasae TG01, and its ability to solubilize insoluble phosphate

Abstract: Abstract. Sudiana A, Putri A, Napitupulu TP, Purnaningsih I, Idris, Kanti A. 2020. Growth inhibition of Fusarium solani and F. oxysporum by Streptomyces sasae TG01, and its ability to solubilize insoluble phosphate. Biodiversitas 21: 429-435. Actinomycetes have been widely explored for new antibiotic production, but not many studies explore its abilities to inhibit the growth of phytopathogenic fungi and solubilize insoluble phosphate hence stimulate the growth of plants. We isolated Actinomycetes from the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…The proportion of active isolates against V. dahlia, recorded in this study, was higher than that obtained by Xue et al (2013). Also, recent studies (Sharma and Manhas 2020;Sudiana et al 2020) have found that F. oxysporum was also sensitive to antagonistic actinobacteria isolated from soil. Genera associated with the selected isolates Morphological and physiological traits are summarized in Table 2.…”
Section: Screening Of Antagonistic Isolatescontrasting
confidence: 80%
See 2 more Smart Citations
“…The proportion of active isolates against V. dahlia, recorded in this study, was higher than that obtained by Xue et al (2013). Also, recent studies (Sharma and Manhas 2020;Sudiana et al 2020) have found that F. oxysporum was also sensitive to antagonistic actinobacteria isolated from soil. Genera associated with the selected isolates Morphological and physiological traits are summarized in Table 2.…”
Section: Screening Of Antagonistic Isolatescontrasting
confidence: 80%
“…Which have shown their efficiency in improving the accessibility of phosphate to plants by laboratory, greenhouse, or field trials (Salcedo et al 2014). Nevertheless, actinobacteria have been extensively studied for their capacity to produce new antibiotics, but few studies have explored their aptitude to solubilize phosphate (Sudiana et al 2020). In this study, a qualitative assessment of phosphate solubilization showed the apparition of a clear solubilization zone around colonies of S. flaveus SO1 and S. enissocaesilis SO2.…”
Section: Phosphate Solubilizationmentioning
confidence: 81%
See 1 more Smart Citation
“…lycopersici, digesting the fungal cell wall composed of chitin [51]. Streptomyces sasae TG01 can inhibit the growth of phytopathogenic fungi Fusarium solani and Fusarium oxysporum by producing secondary metabolites including 2-methyl-1,3-dioxolane as the major constituent [52]. The two most effective bioactive root symbiont Streptomyces strains (H2 and H3) were selected based on in vitro petri plate seedling bioassays (IPSB), effectively controlling the damping-off disease caused by Pythium aphanidermatum as well as behaving as plant growth-promoting rhizobacteria able to increase the fresh and dry weight of tomato plants [53].…”
Section: Discussionmentioning
confidence: 99%
“…Field crops production is affected by plant diseases, fungi are the main cause of damage and quality degradation of harvested products. In this regard, a range of fungal species cause diseases that affect all parts of the plants, including F. oxysporum and F. solani, which are considered as the causal of plant wilting diseases (Sudiana et al, 2020). On the other hand, B. cinerea is one of the most widespread phytopathogenic fungi, it causes a gray mold disease that affects many crops (De Angelis et al, 2022).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%